Temperate facultative cleaner wrasses selectively remove ectoparasites from their client-fish in the Azores - Narvaez, Pauline (2020)
Cleaner fishes are key contributors to the health of fish communities. However, much of the information in the literature refers to tropical systems, while fewer studies have examined the activity of cleaner fish inhabiting temperate ecosystems. Facultative cleaner fish are assumed to clean only during their juvenile phase, and have a broader diet than obligatory cleaner fish. Here, we focused on 2 facultative cleaner fish species, Coris julis and Thalassoma pavo, that live along the temperate coasts of the Azorean island of São Miguel. We found that these species focused their cleaning activities on relatively few species of clients, which supports the general idea that facultative cleaner fishes in temperate waters are less dependent on cleaning interactions than obligatory cleaner fishes in tropical waters. Both cleaner species were found to give more bites per host when inspecting larger clients, likely because the latter typically host more parasites. We found that C. julis consumed a greater diversity of food items, which included gnathiid larvae and fewer caligid copepods, compared to T. pavo where no ectoparasites were found. All cleaner fish that we collected after observations of cleaning had eaten gnathiid isopod larvae but not caligid copepods, even though caligid copepods were the most abundant ectoparasite found on the body of 7 selected fish species (including both client and non-client species), suggesting that both species selectively feed on gnathiid isopods. This study is the first to demonstrate that temperate facultative cleaner fish species actively and selectively inspect and remove ectoparasites from their client-fish species.